The Effectiveness of Blended-Discovery Learning Model in Improving Mastery of Acid-Base Concepts - Fitri Meliniasari; Emmawati Sofya; Tasfiri Efkar (Jurnal Pendidikan dan Pembelajaran Kimia, 2022)
This study aims to describe the effectiveness of blended-discovery learning in increasing mastery of acid-base concepts. The method in this study is a quasi-experimental design with a non-equivalent control group design. The population in this study were all students of class XI MIPA at SMA Negeri 13 Bandar Lampung in the academic year 2021/2022. Sampling was done using random sampling technique so that the experimental class was obtained, namely class XI MIPA 3 which was given learning treatment using a blended-discovery learning model and class XI MIPA 1 as a control class using conventional blended-learning. Based on the results of the difference in the two averages (t-test) conducted, the average n-Gain mastery of the acid-base concept of students in the control class was 0.42 with the "medium" category and in the experimental class was 0.74 with "high" category. The results of the effect size test show that 86.5% of the increase in the mastery of the acid-base concept of students in the experimental class is influenced by blended-discovery learning with the help of a virtual laboratory. Based on the results of data analysis conducted, it can be concluded that the blended-discovery learning model is effective and has a "big" influence in increasing students' mastery of acid-base concepts.